Rancang Bangun Website Reservasi Ramadhan Futsal Cilacap Dengan Metode Rapid Application Development - Wisnu Wardana, Mohammad Adiyudha; Saputra, Wahyu Andi (Institut Teknologi Telkom Purwokerto, 2023)
Futsal is a sport that is also popular with soccer players or fans. This sport aims to score as many goals as possible into the opponent's goal, just like soccer. The futsal field which is smaller than soccer allows it to be played indoors or outdoors, in this case several enterprise provide futsal field rental services, one of which is Ramadhan Futsal located in Cilacap Regency, Central Java. The Ramadhan Futsal field reservation process still uses conventional methods by coming directly to the field or through whatsapp media, the payment process is also by coming directly to the location. The reservation process requires extra time and costs in traveling to the location. Based on these problems, this research proposes a solution in the form of a futsal field reservation web design. The development method used is Rapid Application Development with iteration in design step. The implementation process with PHP language assisted with Laravel framework and SQL database. Testing is conducted using the black-box testing method to Ramadhan Futsal worker and Visitor, from 20 stages of testing, all of the tests were declared as success.